2012
DOI: 10.1371/journal.pone.0050557
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Alpha Arrestins Link Activated Seven Transmembrane Receptors to Nedd4 Family E3 Ubiquitin Ligases and Interact with Beta Arrestins

Abstract: The complement of fungal cell surface proteins is widely regulated by ubiquitination of membrane proteins, which results in their endocytosis and vacuolar degradation. For diverse fungal transporters, the specificity of ubiquitination is conferred by alpha arrestin adaptors, which recruit the Nedd4 family E3 ubiquitin ligase Rsp5. A recent study showed that one mammalian alpha arrestin also mediates ubiquitination and lysosomal trafficking of an activated plasma membrane receptor. Here we first screen all five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(97 citation statements)
references
References 60 publications
(118 reference statements)
5
77
0
1
Order By: Relevance
“…The same type of model could apply in other contexts. In the case of b2AR (b2-adrenergic receptor), challenging results suggest that b-arrestin 2, as well as ARRDC3, are necessary for Nedd4-dependent ubiquitylation and degradation of the receptor after its activation by isoproterenol (Han et al, 2012;Nabhan et al, 2010;Shea et al, 2012;Shenoy et al, 2008;Shenoy et al, 2001). Therefore, and in accordance with our hypothesis, it is tempting to speculate that b-arrestin 2 and ARRDC3 (like b-arrestin 1 and ARRDC1 in our case) could heterodimerize to fulfil this scaffolding function.…”
Section: Comparison With the Drosophila Modelsupporting
confidence: 86%
“…The same type of model could apply in other contexts. In the case of b2AR (b2-adrenergic receptor), challenging results suggest that b-arrestin 2, as well as ARRDC3, are necessary for Nedd4-dependent ubiquitylation and degradation of the receptor after its activation by isoproterenol (Han et al, 2012;Nabhan et al, 2010;Shea et al, 2012;Shenoy et al, 2008;Shenoy et al, 2001). Therefore, and in accordance with our hypothesis, it is tempting to speculate that b-arrestin 2 and ARRDC3 (like b-arrestin 1 and ARRDC1 in our case) could heterodimerize to fulfil this scaffolding function.…”
Section: Comparison With the Drosophila Modelsupporting
confidence: 86%
“…For instance, Bul1/2 has a critical role in ubiquitinating and sorting the Gap1 transporter to the vacuole, whereas Art1 plays a critical role in trafficking the Mup1 transporter (Helliwell et al 2001;Soetens et al 2001;Lin et al 2008). In mammalian cells, ARRDC3 controls ubiquitination and down-regulation of b2 and b3 adrenergic receptors as well as the b4 integrin (Draheim et al 2010;Nabhan et al 2010;Patwari et al 2011;Shea et al 2012). Recent studies have shown that some a-arrestin proteins are regulated by phosphorylation, in particular kinases downstream from Tor1, thus allowing cell global regulation of plasma membrane protein levels in response to nutrient status (MacGurn et al 2011;Merhi and Andre 2012).…”
Section: Ubiquitin-dependent Sorting In Endocytosismentioning
confidence: 99%
“…These arrestin-related proteins seem in many cases to target their substrates for degradation. In particular, ARRDC3 has been proposed to have a major role in the down-regulation of ␤2-adrenergic receptor in mice and in human cells (13,14,36), although contradictory observations have been reported (15). The human proteome includes nine members of the Nedd4 ubiquitin ligase family (16).…”
mentioning
confidence: 99%